2019
DOI: 10.2147/dmso.s203099
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validation and cross-cultural adaptation of the depression Patient’s Health Questionnaire – 9 in the Romanian population of patients with Type 2 Diabetes Mellitus</p>

Abstract: Purpose: To validate and to evaluate the performance in depression screening of the Patient’s Health Questionnaire – 9 (PHQ-9) for Romanian patients with Type 2 Diabetes Mellitus (T2DM). Patients and methods: In a consecutive-case, population-based, non-interventional study design 107 hospitalized patients with T2DM were enrolled. The PHQ-9 was evaluated in regard to its acceptability, ceiling and floor effect, reproducibility, and test–retest performance. Its validity was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The most used tool is the Patient Health Questionnaire-9 (PHQ-9) in the study of depression; the PHQ-9 has been shown to have good internal consistency and acceptable inter-item correlations, and strong convergent validity with the PHQ-2 (Maroufizadeh et al, 2019 ). Evidence also shows acceptable evidence of validity and reliability in translated versions of the PHQ-9 (Lupascu et al, 2019 ). However, from the two studies of debt and suicide ideation, one employed a Yes/No question in the measure of suicide ideation; a concern that can be raised is that the context of the suicide ideation is lost in the dichotomous choice.…”
Section: Resultsmentioning
confidence: 99%
“…The most used tool is the Patient Health Questionnaire-9 (PHQ-9) in the study of depression; the PHQ-9 has been shown to have good internal consistency and acceptable inter-item correlations, and strong convergent validity with the PHQ-2 (Maroufizadeh et al, 2019 ). Evidence also shows acceptable evidence of validity and reliability in translated versions of the PHQ-9 (Lupascu et al, 2019 ). However, from the two studies of debt and suicide ideation, one employed a Yes/No question in the measure of suicide ideation; a concern that can be raised is that the context of the suicide ideation is lost in the dichotomous choice.…”
Section: Resultsmentioning
confidence: 99%
“…Depression was measured with the nine-item Patient Health Questionnaire (PHQ-9), validated for the Romanian population [ 22 , 23 ] and proven to be a valid screening tool for depression in various settings (i.e., not only in clinical settings, as initially developed) and also for the general population [ 24 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depression 2. Anxiety 1.2 items 2.2 items Not applicable Lupascu et al [ 223 ] Twist et al [ 224 ] Udedi et al [ 225 ] Zhang et al [ 226 ] Patient Health Questionnaire (PHQ)-9 English General population Depressive symptoms Depression Depressive symptoms/ depression 9 items in total Not applicable Klis et al [ 27 ] Pictorial Representation of Illness and Self Measure Revised II (PRISM-RII) Dutch Diabetes patients Diabetes-related suffering 1. Self illness separation (SIS) 2.Illness perception measure Not applicable The PRISM-RII is a visual interactive PROM Duran et al [ 227 ] Questionnaire on Stress in Diabetic Patients (QSD) German Diabetes patients Diabetes distress 1.…”
Section: Resultsmentioning
confidence: 99%